Khoo Kay Kim: an oral history appointment fated not to be - Mohd Noor Merican, Ahmad Murad (New Straits Times Press (M) Bhd, 2019)
History is what happened in the past. And the past can also be fated not to be, at the same time. On the Tuesday morning of May 28, I was initially slotted for an oral history session with Professor Emeritus Khoo Kay Kim, widely regarded as the nation’s historian.